Development and feasibility of a new reduction forceps for mandibular fractures: A technical innovation - Enkh-Orchlon Batbayar; Joost de Beij; Ruud R.M. Bos; Baucke van Minnen (Elsevier, 2021)
This note reports a simple and effective method to reduce mandibular fractures with newly designed fracture reduction forceps. Medical engineers and oral and maxillofacial surgeons discussed the problems related to existing reduction forceps and developed a new forceps. The forceps prevents lingual flaring by its special design, provide complete anatomical reduction under a tension of the forceps, makes IMF unnecessary in non-comminuted cases, allows precise application of plates, saves table assistance and operation time.